ANALISIS KEMAMPUAN KONEKSI MATEMATIS MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DITINJAU DARI KONEKSI REPRESENTASI DAN KONEKSI PROSEDURAL - Siti Dwi Ifa Rochmawati; Junarti Junarti; Ifa Khoiria Ningrum (Journal of Mathematics Education and Science, 2020)
This article aims to determine the extent of the mathematical connection ability of the linear equations system of two variables in terms of the connection representation and procedural connections. This type of research uses a qualitative approach. This study's subjects were the students of class X MIPA 1 MA P2K Al Hidayah Lajukidul, which numbered 24 students. However, only six subjects were taken based on the level of mathematical connection ability high, medium, and low that had been selected by mathematics subject teachers based on students' ability to solve math story problems. The research instrument consisted of tests and interview questions. Data analysis techniques using the model of Miles and Huberman include data reduction, data presentation, and concluding. The study results showed that in question no. 1, all research subjects can represent connections and procedural connections, students can write mathematical symbols and answer questions using formulas correctly. In problem no.2, only the subject of high mathematical connection ability can connect representation and procedural connections. The other subject is not quite right in writing mathematical symbols. In question no.3, only subjects with low mathematical connection ability do not have representation and procedural connection skills; students only write what is known but is incomplete. In conclusion, the two-variable linear equation system's mathematical connection ability in terms of the connection representation and procedural connections are not evenly distributed. Artikel ini bertujuan untuk mengetahui sejauhmana kemampuan koneksi matematis materi sistem persamaan linear dua variabel ditinjau dari koneksi representasi dan koneksi prosedural. Jenis penelitian ini menggunakan pendekatan kualitatif. Subjek penelitian ini adalah siswa kelas X MIPA 1 MA P2K Al Hidayah Lajukidul yang berjumlah 24 siswa tetapi hanya diambil 6 subjek berdasarkan tingkat kemampuan koneksi matematis tinggi, sedang, dan rendah yang telah dipilih oleh guru mata pelajaran matematika berdasarkan kemampuan siswa dalam menyelesaikan soal cerita matematika. Instrumen penelitian terdiri dari soal tes dan wawancara. Teknik analisis data menggunakan model Miles dan Huberman meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pada soal no. 1 semua subjek penelitian mempunyai kemampuan koneksi representasi dan koneksi prosedural, siswa mampu menuliskan simbol matematika dan menjawab soal menggunakan rumus dengan benar. Pada soal no.2 hanya subjek kemampuan koneksi matematis tinggi yang mempunyai kemampuan koneksi representasi dan koneksi prosedural, subjek yang lain kurang tepat dalam menuliskan simbol matematika. Pada soal no.3 hanya subjek kemampuan koneksi matematis rendah yang belum mempunyai kemampuan koneksi representasi dan prosedural, siswa hanya menuliskan apa yang diketahui tetapi tidak lengkap. Kesimpulannya kemampuan koneksi matematis materi sistem persamaan linear dua variabel ditinjau dari koneksi representasi dan koneksi prosedural belum merata.